The Contribution of Genetic Variants to the Risk of Papillary Thyroid Carcinoma in the Kazakh Population: Study of Common Single Nucleotide Polymorphisms and Their Clinicopathological Correlations - Mussazhanova, Zhanna; Rogounovitch, Tatiana I.; Saenko, Vladimir A.; Krykpayeva, Ainur; Espenbetova, Maira; Azizov, Bauyrzhan; Kondo, Hisayoshi; Matsuda, Katsuya; Kalmatayeva, Zhanna; Issayeva, Raushan; Yeleubayeva, Zhanar; Madiyeva, Madina; et al. (Frontiers in Endocrinology, 2021)
Objective: Risk for developing papillary thyroid carcinoma (PTC), the most common endocrine malignancy, is thought to be mediated by the lifestyle, environmental exposures and genetic factors. Recent progress in the genome-wide association studies of thyroid cancer lead to the identification of several genetic variants conferring risk to this malignancy across different ethnicities. We set out to elucidate the impact of selected single nucleotide polymorphisms (SNPs) on PTC risk, and to evaluate clinicopathological correlations of these genetic variants in the Kazakh population for the first time. Methods: Eight SNPs were genotyped in 485 patients with PTC and 1008 healthy control Kazakh subjects. The association analysis and multivariable modeling of PTC risk by the genetic factors, supplemented with rigorous statistical validation, were performed. Result: Five of the eight SNPs: rs965513 (FOXE1/PTCSC2, P=1.3E-16), rs1867277 (FOXE1 5’UTR, P=7.5E-06), rs2439302 (NRG1 intron 1, P=4.0E-05), rs944289 (PTCSC3/NKX2-1, P=4.5E-06) and rs10136427 (BATF upstream, P=9.8E-03) were significantly associated with PTC. rs966423 (DIRC3, P=0.07) showed a suggestive association. rs7267944 (DHX35) was associated with PTC risk in males (P=0.02), rs1867277 (FOXE1) conferred the higher risk in subjects older than 55 years (P=7.0E-05), and rs6983267 (POU5F1B/CCAT2) was associated with pT3-T4 tumors (P=0.01). The contribution of genetic component (unidirectional independent effects of rs965513, rs944289, rs2439302 and rs10136427 adjusted for age and sex) to PTC risk in the analyzed series was estimated to be 30-40%. Conclusion: Genetic factors analyzed in the present work display significant association signals with PTC either on the whole group analysis or in particular clinicopathological groups and account for about one-third of the risk for PTC in the Kazakh population.